The Effect of Variations in Mung Bean Sprout Extract (Tauge) on the Organoleptic Quality of Fermented Beverage from Pineapple Juice (Ananas comosus, L.Merr) - Centhya Victorin Maitimu (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
Fermented pineapple juice beverage is a biotechnology product obtained through a natural fermentation process. This study aims to determine the effect of varying additions of mung bean sprout extract (tauge) on the organoleptic quality of fermented pineapple juice, including color, aroma, taste, and overall preference. The method used was a quantitative experimental design with four treatments: P0 (control, 1000 ml pineapple juice), P1 (750 ml pineapple juice + 250 ml sprout extract), P2 (500 ml pineapple juice + 500 ml sprout extract), and P3 (250 ml pineapple juice + 750 ml sprout extract). Organoleptic tests were conducted by 20 panelists using a 1–4 hedonic scale. The analysis results showed that treatment P3 received the highest scores for color (2.85) and aroma (2.00), indicating a slightly bright yellow color and an aroma still resembling pineapple. For taste and overall preference, treatment P1 received the highest scores with a taste score of 2.75 (moderately sweet to sweet) and a preference score of 3.15 (liked). It can be concluded that the addition of mung bean sprout extract (tauge) affects the organoleptic quality of fermented pineapple juice. Treatment P1 provided the best balance of aroma, taste, and panelist preference. The results suggest that a 3:1 ratio of pineapple juice to mung bean sprout extract (P1) can be recommended as the optimal formulation to enhance the nutritional value and flavor of fermented pineapple beverages.